IMPLEMENTATION OF THE DISTRIBUTION OF NON-CASH FOOD ASSISTANCE PROGRAM THROUGH CISAAT POST OFFICE IN 2022 - Rismayanti Amalia; Rijal Amirulloh; Rizki Hegia Sampurna (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The purpose of this study was to determine the implementation of the distribution of the Non-Cash Food Assistance Program through the Cisaat Post Office in 2022. The method used is a qualitative research method with a descriptive approach. Data collection techniques include observation, interview, and documentation. Data analysis uses an interactive model, namely data reduction, data presentation and verification. Data validation uses technical triangulation and source triangulation. This research uses four policy implementation variables according to George Edward III, namely Communication, Resources, Disposition, and Bureaucratic Structure. The results showed that the implementation of the distribution of non-cash food assistance programs through the Cisaat Post Office in 2022. shows that the distribution of the program has been carried out well, but in its implementation there are still obstacles. In the resource dimension, namely the lack of human resources at the Cisaat post office. So that the Cisaat post office recruits a jubar or paymaster to help the process of distributing Non-Cash Food Assistance.